A Study of Variation in the Tube Feeding Rate by Nurses in a Tertiary NICU - Krishnegowda, Sushma; Vasudev, Prajwala Hassan; Doreswamy, Srinivasa Murthy; Veena, S.; Hemavathi, M. (Journal of Nepal Paediatric Society, 2017)
Introduction: 50-60% of the low birth weight babies in a neonatal unit are on gravity feed via gavage tube as they often are not strong enough to sustain on oral feeds. Successful feeding depends on nursing skill and individual variation can be expected. As with many other nursing practices in NICU, considerable variation can be expected in gravity feeding rate as well. The objective was to determine the intra individual and inter individual variation in the rate of gravity feeding among the nurses. Material and Methods: This was a Prospective study done in a Tertiary Neonatal care unit. Babies weighing < 2 kgon enteral feeds were included in study. The nurses carried out feeding in the standard prescribed manner. Time taken for feeds was noted. Results: 21 nurses participated in the study. 15 babies were included and there were 342 feed events. During 75(22%) feeding events, the nurses had an assignment of less than four babies. During rest of the 267 (78%) feeding events, they had more than four babies assigned for care. The median volume of feed was 14 ml and median duration was 8 minutes. Feeding rate variation within same nurse varied from one to 37.5 times their base line rate and in between the nurses varied by minimum of 17 times. Conclusion: A wide intra and interpersonal variation among the nurses, with respect to the rate of feeding of newborns was observed in our study.